Abdominal cavity unidirectional shunt for refractory pericardial effusion 7 months after cardiac valve replacement: A case report. Issue 1 (14th October 2020) - Chen, Jingwei; Zhong, Ruhe; Qiu, Longxing; Liang, Qing; Li, Hua; Liu, Huajian; Yuan, Jian
Abstract: Refractory pericardial effusion after repeated pericardial drainage and drug therapy for nearly half a year after cardiac valve replacement is rare. We present the case of a 36‐year‐old female patient who underwent an abdominal cavity unidirectional shunt for refractory massive pericardial effusion through a subxiphoid mini‐incision, 7 months after cardiac valve replacement. The head end of a prefabricated bovine pericardial short tube with double leaflets on the tail was sutured to the small incised hole of the diaphragm, whereas the body and the tail of the short tube were dissociated in the left anterior hepatic space. Three months later, the pericardial effusion completely disappeared, no peritoneal effusion occurred, and all symptoms vanished.